Kitacon Sdn. Bhd. / Dainel Aidil Jamaluddin - Jamaluddin, Dainel Aidil (Faculty Of Civil Engineering, 2015)
This report is about the economic section and the technical section in site. The economic section contains the company profile. Kitacon Sdn. Bhd. is a contractor that have big name around Selangor and Kuala Lumpur. This company provide industrial building and warehouses. Kitacon Sdn. Bhd. was incorporated in 1990 .The program include site visits, quarterly auditing at site, attending monthly progress meeting, drawing part and calculation part that related with civil engineering. At the end of this program, the trainee has gained valuable working experience and knowledge both in technical and administration section, and also managed to complete the program successfully. The trainee has been brought to Syeksen Ul, Temasya Glenmarie, Shah Alam in Selangor for site visit in order to gain real industrial knowledge and experiences in scheduled waste management.